Auditory category knowledge in experts and novices - Heald, Shannon L. M.; Van Hedger, Stephen C.; Nusbaum, Howard C. (Frontiers in Neuroscience, 2014)
What do listeners know about sounds that have a systematic organization? Research suggests that listeners store absolute pitch information as part of their representations for specific auditory experiences. It is unclear however, if such knowledge is abstracted beyond these experiences. In two studies we examined this question via a tone adjustment task in which listeners heard one of several target tones to be matched by adjusting the frequency of a subsequent starting tone. In the first experiment listeners estimated tones from one of three distributions differing in frequency range. The effect of tone matching in the three different distributions was then modeled using randomly generated data (RGD) to ascertain the degree to which individuals’ estimates are affected by generalized note knowledge. Results showed that while listeners’ estimates were similar to the RGD, indicating a central tendency effect reflective of the target tone distribution, listeners were more accurate than the RGD indicating that their estimates were affected by generalized note knowledge. The second experiment tested three groups of listeners who vary in the nature of their note knowledge. Specifically, absolute pitch (AP) possessors, non-AP listeners matched in musical expertise (ME), and non-AP musical novices (MN) adjusted tones from a micro-scale that included only two in-tune notes (B4 and C5). While tone estimates for all groups showed a central tendency effect reflective of the target tone distribution, each groups’ estimates were more accurate than the RGD, indicating all listeners’ estimates were guided by generalized note knowledge. Further, there was evidence that explicit note knowledge additionally influenced AP possessors’ tone estimates, as tones closer to C5 had less error. Results indicate that everyday listeners possess generalized note knowledge that influences the perception of isolated tones and that this effect is made more evident with additional musical experience.